Effect of SandBall Tool Modification on Sideways-Style Bullet Repellent Learning Outcomes of Junior High School Students - Wisnu Guntur Sutopo; Fajar Azizah; Romy Abdul Rozak (JUMORA: Jurnal Moderasi Olahraga, 2022)
This study was conducted to improve the learning outcomes of sideways-style bullet repellent material with modifications to sandball aids in junior high school students. This research is a class action study. The subjects in this study were 30 junior high school students. This study was conducted starting May 30, 2020. The purpose of this study is to improbullet-repellent the learning outcomes of sideways-style bullet repellent using sandball aids in junior high school students. With this research, it is hoped that it can be used as reference material for teachers regarding the use of sandball aids for learning sideways-style bullet repellent in general and especially in junior high school students. The results of learning on bullet-repellent material with a sideways style have increased by using sandball aids. And from the results of the research analysis in cycle I of students who have not completed there are 18 people and those who have completed 12 people, after the implementation of cycle II, it is known that there is an increase of 41.95%. This shows that the use of sandball aids on bullet-repellent material can improve learning outcomes in junior high school students.  Based on the findings and discussions, it was concluded that there was an influence of the modification of the sandball tool on the learning outcomes of sideways-style bullet repellent for junior high school students.  Contributions to future research are recommended to be able to develop various learning models, methods, and approaches including the application of modifications because basically these elements in physical education will always be proud in accordance with the demands of the times. Keywords: Bullet Repellent, Sand Aids, Improvement of Learning Outcomes.